Silhouette sign of chest X-ray – a rescue sign of a lung carcinoma that almost missed - Shalihin, Mohd Shaiful Ehsan; Harun, Zulkifli; Osman, Iskandar Firzada; Mukhali, Hassan Basri (2018)
 Lung carcinoma typically presents with haemoptysis and constitutional symptoms on a background history of chronic cigarette smoking.  A chest X-ray can pick up these lesions in view of its radio-opacity and nodular appearances that are manifested in more than 90% of cases.1  However it can be mistakenly interpreted as normal if it is obscured by heart shadow.  Nevertheless, loss of a specific contour can help determine the presence position of a disease process. This phenomenon is known as the silhouette sign